Raznolikost v farmakološkem odzivu na zdravljenje z metforminom - Ornik, Vanja (Zdravniški vestnik, 2013)
Background: According to the Slovenian guidelines,metformin, an oral antidiabetic drug, is adrug of choice for the treatment of type 2 diabetes.Additionally, metformin is paving its wayin polycystic ovary syndrome (PCOS) treatment,although the drug has not (yet) been officially indicatedto treat PCOS. Studies have shown thatmetformin improves clinical and biochemicalfeatures of PCOS as well as the rate of ovulationand consequently the likelihood of conceptionin PCOS women. At the same dosage regimen,pharmacological effects of metformin show interindividualvariability in metformin response;efforts have been made to at least partly explainthe variability with polymorphic variants ingenes related to metformin pharmacodynamicsand pharmacokinetics.Conclusions: The results of the current studiesindicate that polymorphic variants in genesrelated to metformin pharmacodynamics andpharmacokinetics may contribute to the interindividualvariability in pharmacological responseto metformin treatment in diabetic as well as inPCOS patients
Keywords: farmakogenetika; farmakoterapija; genetic polymorphisms; genetski polimorfizmi; pharmacogenetics; pharmacotherapy; polycystic ovary syndrome; sindrom policističnih jajčnikov; sladkorna bolezen tipa 2; type 2 diabetes